Uji Daya Hasil Galur Generasi F3 Padi Beras Merah (Oryza sativa L.) - Muliarta Aryana; yurnawati Yurnawati; Sutresna Wayan Sutresna (LPPM Universitas Mataram, 2018)
The aim of this research was to know the potential of several lines of F3 generation of new red rice from the crossbreeding of Fatmawati and IPB3S varieties with red rice. The research was conducted in Nyurlembang Village, Narmada District, West Lombok Regency, West Nusa Tenggara Province, with elevation of ± 127 m above sea level from July to October 2017. The experiment design was Randomized Block Design (RAK) with 25 treatments i.e. 20 red rice lines, three parents and two comparator varieties. The result shows that all observed characters were significant differences. There are 13 lines of 20 red rice lines have high yield potential above the average yield of the parent and comparator varieties are G17, G9, G18, G13, G12, G15, G8, G14, G7, G11, G6, G19 and G20:11.30 ton.ha-1, 9.44 ton.ha-1, 9.21 ton.ha-1, 9.17 ton.ha-1, 8.94 17 ton.ha-1, 8.92 ton.ha-1, 8.89 ton.ha-1, 8.88 ton.ha-1, 8.81 ton.ha-1, 8.67 ton.ha-1, 8.38 ton.ha-1, 8.12 ton.ha-1and 8.10 ton.ha-1 respectively